BALANCED SCORECARD: ALAT UKUR KINERJA DESA WARINGIN JAYA DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN - Lestari, Wulan; Azka, Aditya Fadillah; Agustine, Vinna Ayu; Novita, Novita (Universitas Trilogi, 2024)
The allocation of Village Funds (ADD) must be balanced with the achievement of good performance by producing outputs and benefits that can be felt tangibly by all levels of villagers. The purpose of this study is to help the government in Waringin Jaya Village determine the performance measure of institutions by using a balanced scorecard that is balanced with public service standards in achieving good governance. The method in this research is qualitative descriptive with data collection techniques, namely interviews, questionnaires, observations and documentation. This research produces a balanced scorecard design with the perspective of service to the community as the main measure and supported by financial perspectives, internal processes, as well as growth and learning based on the principles of good governance. This design is expected to be a measure of the performance of the Waringin Jaya Village government in realizing good community services and community welfare development from the allocation of village funds received from the central government. Keywords: Public Sector Organisations, Balanced scorecard, Public Services, Governance